An elderly case of aortic stenosis associated with double-chambered right ventricle. Issue 4 (April 2023) - Yasumoto, Yuto; Nakamura, Yoshitsugu; Ushijima, Masaki; Yoshiyama, Daiki; Kuroda, Miho; Sawa, Shintaro; Nakayama, Taisuke; Narita, Takuya; Furutachi, Akira; Tsuruta, Ryo; Ito, Yujiro
Abstract: Double-chambered right ventricle (DCRV) caused by right ventricular outflow tract obstruction, is a developmental cardiac anomaly in which the anomalous muscle bundles divide the right ventricular cavity into two chambers. Few cases with DCRV coexisting with severe aortic stenosis (AS) have been reported. Moreover, adult cases are extremely uncommon. We report an elderly case of a heavy DCRV with severe AS detected by transthoracic echocardiography and catheterization study. An 85-year-old woman with dyspnea on effort and right-sided heart failure was diagnosed with DCRV and severe AS by echocardiography. She underwent a resection of the anomalous muscle of the right ventricle and aortic valve replacement. Her symptoms disappeared postoperatively and was discharged home. At 2 years postoperatively, she was generally well without recurrence of DCRV. In conclusion, the case of DCRV with AS is rare and surgery is useful to relieve the heart failure symptoms and improve the prognosis of both young and adult patients. Learning objective: Double-chambered right ventricle (DCRV) is uncommon in the older population; however, clinicians should consider DCRV in patients with right-sided heart failure as a differential diagnosis. The case of DCRV with aortic stenosis is rare, surgical treatment is particularly useful for these patients to relieve the heart failure symptoms and improve the prognosis in young and adult cases.